Antimutagenic activity of cashew apple (Anacardium occidentale Sapindales, Anacardiaceae) fresh juice and processed juice (cajuína) against methyl methanesulfonate, 4-nitroquinoline N-oxide and benzo[a]pyrene - Melo-Cavalcante,Ana Amelia (2008)
Cashew apple juice (CAJ), produced from the native Brazilian cashew tree (Anacardium occidentale), and has been reported to have antibacterial, antifungal, antitumor, antioxidant and antimutagenic properties. Both the fresh unprocessed juice and the processed juice (cajuína in Portuguese) has been shown to consist of a complex mixture containing high concentrations of anacardic and ascorbic acids plus several carotenoids, phenolic compounds and metals. We assessed both types of juice for their antimutagenic properties against the direct mutagens methyl methanesulfonate (MMS) and 4-nitroquinoline-N-oxide (4-NQO) and the indirect mutagen benzo[a]pyrene (BaP) using pre-treatment, co-treatment and post-treatment assays with Salmonella typhimurium strains TA100, TA102, and TA97a. In pre-treatment experiments with strains TA100 and TA102 the fresh juice showed high antimutagenic activity against MMS but, conversely, co-treatment with both juices enhanced MMS mutagenicity and there was an indication of toxicity in the post-treatment regime. In pre-, co-, and post-treatments with TA97a as test strain, antimutagenic effects were also observed against 4-NQO and BaP. These results suggest that both fresh and processed CAJ can protect the cells against mutagenesis induced by direct and indirect mutagens.